Textbook Analysis of Pancasila and Civic Education and Curriculum in State Vocational High School 6 Palu - Jamaludin Jamaludin; Riska Tambidjonga; Juisda Elisabet; Isti Qumaira; Nurhadija Nurhadija; Nuralia Hamdan; Intan Triana; Sarwina Ayu Lestari; Umul Astifa; Nadila Yulianingsi; Parigul Parigul; Lisdayani Lisdayani; Gerhana Gerhana; Nur Azizah; Widya Astuti; Rini Wulandari; Shofia Nurun Alanur; Sumawati Sukmawati (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
This study focused on "Analysis of Civics and Curriculum Textbooks" as a Learning Resource for Citizenship Education in Class XI Students of SMK Negeri 6 Palu. The purpose of this research; (1) the contents of PPKn textbook material as a learning resource for class XI students at SMK Negeri 6 Palu (2) the suitability of the material with curriculum updates as a learning resource for class XI students at SMK. The research method uses descriptive qualitative. Data collection techniques used direct communication techniques, direct observation techniques, and documentary techniques. The data collection tools used were interview guides, observation guides, and documentation. The research results show that; contents of PPKn and Curriculum textbook material as learning resources for class XI students of SMK Negeri 6 Palu, namely suitability of material with Competency standards (SK) and Basic Competence (KD), suitability of material with curriculum, accuracy of material, encouraging student curiosity, scientific substance and life skills, as well as enrichment of the benefits of PPKn and Curriculum textbooks as learning resources for class XI Negeri 6 Palu students namely, as serious learning materials, as easy teaching materials, for teachers textbooks mean security, guidance and assistance in the learning process.